On convergence and compactness in parabolic problems with globally large diffusion and nonlinear boundary conditions - Carbinatto, Maria C.; Rybakowski, Krzysztof P. (Topological Methods in Nonlinear Analysis, 2012)
We establish some abstract convergence and compactness results for families of singularly perturbed semilinear parabolic equations and apply them to reaction-diffusion equations with nonlinear boundary conditions and large diffusion. This refines some previous results of [R. Willie, < i> A semilinear reaction-diffusion system of equations and large diffusion< /i> , J. Dynam. Differential Equations < b> 16< /b> (2004), 35-63].